Governing Through Accountability: Gender Equality and the United Nations - Cole, Sally; Phillips, Lynne (Atlantis)

(untitled) (Mount Saint Vincent University, 2008)
This article investigates the audit culture of UNIFEM, an international organization dedicated to bringing about global gender equality. UNIFEM's strategic plans, regional activities, and one fund-raising activity are analyzed to illustrate how pressures to "manage for results" combine with the UN's promotion of a transnational, modernist ethos to shape gender equity policy and, ultimately, what we know about women's lives.